A parallel CPU/GPU algorithm for 3D pose estimation using CUDA and OpenMP - Picos, Kenia (My University, 2016)
Pose recognition is characterized by location and orientation parameters, in which introduces high complexity due the huge number of visualization than a target can present within a scene. Several issues such as noise, incident light sources and geometrical distortions, modify the appearance of a target with respect an observation point, making object recognition a complex task. A design of an effective algorithm is needed in order to analyze the physical phenomena implied in the visualization of a moving 3D object, and to improve the execution performance.
Keywords: Reconocimiento de pose; Parámetros de ubicación; Campus Tijuana